2021
DOI: 10.2196/24828
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Wearable Activity Tracker Use, Exercise Motivation, and Physical Activity in a Cohort of Cancer Survivors: Secondary Data Analysis of the Health Information National Trends Survey

Abstract: Background Cancer survivors who meet physical activity (PA) recommendations (≥150 minutes of moderate-to-vigorous physical activity [MVPA] per week) experience better health outcomes. With the growing availability of wearable activity trackers (WATs), it may be easier to track PA. However, it is unknown what motivates survivors to use these devices. Objective The aim of this study is to investigate the associations among motivations for exercise, previo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…All participants had ongoing access to an activity tracker and companion app that facilitated use of behavioral strategies (e.g., self‐monitoring of behavior, goal setting) throughout the trial period, and YACS have reported that goals help them maintain PA behaviors 55 . Further, cancer survivors who use activity trackers to monitor activity or a health goal are more likely report meeting PA recommendations 56 . Among YACS, lack of social support has been identified as a key barrier to PA adherence, while accountability to others is a facilitator 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants had ongoing access to an activity tracker and companion app that facilitated use of behavioral strategies (e.g., self‐monitoring of behavior, goal setting) throughout the trial period, and YACS have reported that goals help them maintain PA behaviors 55 . Further, cancer survivors who use activity trackers to monitor activity or a health goal are more likely report meeting PA recommendations 56 . Among YACS, lack of social support has been identified as a key barrier to PA adherence, while accountability to others is a facilitator 55 .…”
Section: Discussionmentioning
confidence: 99%
“… 55 Further, cancer survivors who use activity trackers to monitor activity or a health goal are more likely report meeting PA recommendations. 56 Among YACS, lack of social support has been identified as a key barrier to PA adherence, while accountability to others is a facilitator. 55 It is possible that the Facebook group was sufficient for some participants in both groups to enhance social support and accountability.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of WD use may play a role in promoting positive health changes. Previous works examining the role of wearable healthcare devices in facilitating physical activity have mainly focused on the association between ever-users vs. non-users of WD and physical activity engagement [ 28 , 44 ]. These studies indicated that simply using wearable devices may promote physical activity among adults.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, there were 9 patients who had missing items on the primary end points and were omitted in the analysis, but the proportion of patient with missing and the baseline self-reported LTPA were similar between intervention and control. Sixth, while WAT could be used for individualized PA intervention regardless of type of cancer or treatment [ 69 ], the individual PA counseling should be performed considering cancer- and cancer treatment-related factors. However, the study included only patients who were scheduled to receive RT for breast cancer at a single center, which may limit the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 99%